Peculiarities of formation and clinical course of symptomatic epilepsy as a result of cranial injury - A. O. Kaptalan; A. N. Stoyanov; I. O. Ostapenko; V. V. Kirchev; P. P. Yermuraki (Kazimierz Wielki University, 2021)
Post-traumatic epilepsy (PTE) is a formidable and frequent consequence of traumatic brain injury (TBI) in the long term. 41 patients with PTE were examined, mostly men of working age. The time of formation of PTE after was 14.3 ± 1.4 months, which decreased depending on the severity of brain injury, the average frequency of seizures was 2.93 ± 0.8 per month. Focal seizures were mainly registered (63.4%, p <0.05), and taking into account the focal onset in bilateral tonic-clonic seizures, this figure reached 90.2% (p <0.05). Among the selected syndromes, except for direct PTE, autonomic dysfunctions (87.8%) with paroxysmal course (58.5%) prevailed, especially in persons with moderate trauma (r = 0.51, p <0.05). Typical comorbid symptoms in people with PTE were cognitive deficits, which correlated with the severity of TBI, as well as depressive and anxiety symptoms. Depressive layers were more often observed in the presence of the focal component of seizures (94.7%, p <0.05), temporal localization of the pathological process and predominant vagotonia. Anxiety manifestations affected all types of attacks on the background of sympathicotonia (83.3%, p <0.05), which in our opinion improved the implementation of crisis conditions, which were observed in 66.7% of cases.